Mapping active strain using terahertz metamaterial laminates - Omar Khatib (AIP Publishing LLC, 2021)
The ability to image strain fields in composite materials is an indispensable necessity for structural health monitoring. Embedded electromagnetic metamaterials sensitive to applied stresses and operating in the terahertz regime have been proposed as a solution, but they have traditionally relied on slight amplitude or frequency shifts of their terahertz spectral resonance relative to a presumably unchanging, unstrained reference spectral map. Here, we demonstrate a facile, reference-free imaging technique to map the currently active local strain throughout a composite structure using a reversible passive terahertz metamaterial laminate with a tailored polarimetric signature. Only two orthogonal polarizations and a few frequencies are required to measure this strong terahertz response, from which the local strain environment may be rapidly and quantitatively mapped over large areas.